Bring back my Barry to me: Nostalgia for Barack Obama and political outcomes. (October 2021) - Fetterman, Adam K.; Wildschut, Tim; Sedikides, Constantine
Abstract: The 2016 election of President Donald Trump left over half of the United States' electorate reeling. This contributed to nostalgia for the days of Barack Obama (and his administration), even among some conservatives and Republicans. We hypothesized that individual differences in nostalgia for Barack Obama would predict outcomes in the political arena. Consistent with the hypothesis, in three studies ( N = 904), Obama nostalgia predicted negative attitudes toward the Trump presidency, stronger political engagement intentions and voting intentions, and actual political engagement, above and beyond competing predictors (i.e., political ideology, prior support for Donald Trump in the 2016 presidential election, voting behavior in 2016). The findings reinforce the role of nostalgia for a politician or political administration as an influential predictor of political outcomes. We discuss implications and future research directions. Highlights: The election of Donald Trump contributed to feelings of nostalgia for Barack Obama Obama nostalgia predicted negative attitudes toward the Trump presidency Obama nostalgia predicted political engagement and voting intentions Correlations with Obama nostalgia were significant when controlling for ideology